THU0254 Residual Inflammatory Activity Assessed by A Multi-Biomarker Disease Activity Blood Test is Linked to Structural Damage in RA Patients in Low Disease Activity/Remission and Normal C-Reactive Protein Level. (10th June 2014) - Schett, G.; Finzel, S.; Rech, J.; Sasso, E.H.; Segurado, O.G.
Abstract : Background: The autoantibody positive (AAB+) subset of rheumatoid arthritis (RA) patients is prone to develop bone damage. Since the extent of bone erosion in AAB+ RA shows substantial variation, we hypothesized that, next to AAB, the level of local and systemic inflammation and tissue metabolism is the second factor determining damage. We therefore evaluated inflammation with a multi-biomarker disease activity (MBDA) blood test that measures serum concentrations of 12 inflammatory mediators related to local tissue metabolism and systemic acute phase response. Objectives: Determine the relationship between disease activity in patients with RA, assessed by a MBDA score, and the volume and number of bone erosions, assessed with micro-computed tomography (micro-CT). Methods: 78 AAB+ RA patients in remission or low disease activity (DAS28 <3.2) and with normalized C-reactive protein level (<0.5 mg/dL) were analysed at a single time point. The serum concentrations of 12 biomarkers (SAA, CRP, TNFRI, IL-6, VEGF, EGF, MMP1, MMP3, YKL40, leptin, resistin, VCAM1) were computed in a validated algorithm to produce the MBDA (Vectra®DA) score ranging from 1 to 100. The burden of bone erosion was assessed by high-resolution quantitative micro-computed tomography using an Xtreme-CT scanner. The MBDA score was correlated to the total bone erosion volume (reflecting numbers and size) in the metacarpophalangeal joints. Results: Of the 78 RA patients, 44 (56%) displayed low MBDA scores (<30), 14 (18%) had a medium score (30-44) and 20 (26%) had a high score >44, according to previously defined cut-offs. Erosion volumes were significantly (p<0.001, Kruskal Wallis test) different between the 3 subgroups, with a mean cumulative erosion volume of 1.8 mm 3, 28.0 mm 3 and 21.4 mm 3 in the low, medium and high MBDA categories, respectively. DAS28 scores were low (<3.2) and not significantly different between groups, CRP was normal in all the patients (<0.5 mg/dL) and disease duration and treatments received (non-biologics versus biologics) were equally distributed among the low, medium and high MBDA subgroups. MBDA scores were significantly correlated to erosion numbers (Spearman's r=0.64, p<0.0001) and erosion volumes (r=0.65, <0.0001). Conclusions: These findings suggest that the inflammatory mediators measured by the MBDA blood test detect processes that are linked to structural bone damage in RA. These findings are particularly important for refining the ability to identify patient subgroups that may develop structural damage despite low disease activity. Disclosure of Interest: : G. Schett: None declared, S. Finzel: None declared, J. Rech: None declared, E. Sasso Employee of: Crescendo, O. Segurado Employee of: Crescendo DOI: 10.1136/annrheumdis-2014-eular.2976